Oligochaeta (Annelida) of the profundal of Lake Hazar (Turkey), with description of Potamothrix alatus hazaricus n. ssp. - Timm, Tarmo; Arslan, Naime; Rüzgar, Melih; Martinsson, Svante; Erséus, Christer (Zootaxa, 2013)
Lake Hazar is an alkaline oligotrophic lake of tectonic origin, located in the Eastern Anatolia region in Turkey, 1248 m a.s.l. Its surface area is 80 km2, the average depth 93 m and maximum depth 205 m. The lake and its surroundings are under protection as a region of historical value. During the present study (2007–2012), samples were taken from 15 stations located at a depth of 2–200 m. Oligochaeta comprised 69% of the total invertebrate abundance. The profundal oligochaete fauna was found to consist of only three tubificid taxa, all of the subfamily Tubificinae. Potamothrix alatus hazaricus Timm & Arslan, n. ssp. was dominating anywhere down to maximum depths while Psammoryctides barbatus (Grube) and Ilyodrilus(?) sp. occurred seldom. All three are new records for Lake Hazar. Potamothrix alatus hazaricus shares the "winged" body shape in its genital region with the nominal, brackish-water subspecies P. a. alatus Finogenova, 1972, and the lateral position of the spermathecal pores and the shape of the ventral chaetae with the freshwater subspecies P. a. paravanicus Poddubnaja & Pataridze, 1989 known from Transcaucasian lakes. The mitochondrial COI barcoding gene suggests long separation between the two taxa, but the nuclear ITS region shows no variation. The generic position of Ilyodrilus (?) sp. remains obscure since its internal genitalia could not be studied.